Desarrollo de una aplicación web para Bancos Comunitarios en el Cantón El Chaco utilizando Test Driven Development - Torres Marroquin, Ruben Dario (2025)
The research focuses on the development and evaluation of the security of a web application for Community Banks in the Cantón El Chaco, using the Test Driven Development (TDD) methodology. It was identified that the problem lay in the manual management of financial transactions, which made it difficult to analyze and track data, as well as compromising the security of the transactions. The proposed solution was to develop the application using TDD to ensure a robust construction and early detection of errors. The development was carried out using technologies such as .NET Core 8, Angular, and PostgreSQL, enabling a flexible and secure architecture. The Kanban methodology was employed for agile project management. The research had a quantitative approach, which allowed for the evaluation of the application's security according to the ISO/IEC 25010 standards, focusing on critical aspects such as authenticity, confidentiality, and data integrity. The results of the security tests, conducted with a quantitative approach, showed significant improvements: in authenticity, vulnerabilities decreased from 32 to 12, representing a 62.5% improvement; in confidentiality, vulnerabilities decreased from 18 to 6, achieving a 66% improvement; and in integrity, vulnerabilities decreased from 25 to 8, with a 68% improvement. These results demonstrate the effectiveness of TDD strategies in mitigating security risks and ensuring data protection. These results highlight the effectiveness of TDD strategies in mitigating security risks and ensuring data protection, largely attributable to the tools used, such as .NET Core 8, Angular, and PostgreSQL, which were fundamental in achieving the improvement in the application's security.